Application of the Principle of Fairness in the Distribution of Rewards: Evidence from Serbia and Bosnia & Herzegovina - Ivan Kostadinovic; Azra H. Hanic; Darko B. Vukovic (Institute of Economic Research (IER), 2017)
In the search for additional data, which would enable the conclusion on the implementation of the principle of fairness in the distribution of rewards as one of the key ethical concepts in relations between employers and employees, a survey was conducted, which entailed the corresponding proportional number of respondents from Serbia and Bosnia and Herzegovina, to enable comparison of results. On the basis of secondary data, this research started from the assumption that the principle of Procedural justice in the distribution of income in Serbia and B&H has been insufficiently applied in practice in organizations in these two countries. It has been assumed that the ownership structure of the company (organization) affects the degree of implementation of the principles of fairness. The aim of this paper is to identify elements of the system of rewards which determine the perception of fairness among employees and to what extent they are implemented in organizations in Serbia and Bosnia and Herzegovina. In this paper the authors are looking for the identification of elements that form the basis of fairness in the distribution of rewards and their importance for the perception of fairness. Methodologically, the paper is based on the analysis of the existing literature, secondary sources and statistically processed results of the survey conducted in 328 organizations in Serbia and Bosnia and Herzegovina. The results of this analysis indicate that the elements of fairness in distribution of rewards were neglected in the organizations analyzed in this research. According to the presented data of the research conducted on the sample of 325 respondents in Serbia and Bosnia and Herzegovina hypotheses are confirmed that the principles of procedural justice are not sufficiently applied in organizations in Serbia and Bosnia and Herzegovina. Their application depends on the form of ownership. Low perception of procedural practice in distribution of rewards may have negative impact on business results, which can be the subject of some future research.
Keywords: M12; M50; M51; M54; 330; fairness; rewards; employees; organizational justice; behavior